ENT600 : Magic paraffin wax filter / Intan Suraya Mohd Yunus … [et al.] - Mohd Yunus, Intan Suraya; Zakaria, Erdayu @ Erzatul Rahayu; Mohd Sapuan, Siti Haida; Abdul Manan, Nur Ewani; Tajidin, Syazwani; Hashim, Norjannatun Nairn (2015)
Paraffin wax heat therapy bath is one of the moist heat therapy modalities that have been used in the physiotherapy clinics. This modality speeds healing, and soothes soft tissues and muscle pains. An additional benefit of paraffin wax bath therapy is that on top of its function as a therapy modality and heat, the wax itself soothes and moisturizes the human body, the skin, opens pores, increasing blood flow, circulation and creates a general sense of relaxation and calm effect on the patients. Paraffin wax is a natural component of crude mineral oils, produced by refining or separating the wax out of the crude mineral oils. To purify it, it has to be boiled, then cooled, then filtered into a heavy wax-oil substance, finishing as the paraffin wax. It is laboratory tested to be safe for external use, and hygienic. The wax that has been used is colorless, tasteless, and unscented. Also, it is heavy in molecular structure, increasing blood supply to the body part being treated, trapping moisture from the underlying layers of the skin - this results in a rejuvenating, moisturizing and nourishing effect on the skin, the often soft and smooth finishing on the skin. Nowadays, there is a lot of patient enter rehabilitation department for the wax treatment. Infection control is the key settings in hospital and the wax that has been used by the patient should be recycled for reuse to maximize the use as the expensive price. But the procedure of cleaning is different follow by their Department. Our team has chosen a product that we believe can help all rehabilitation departments towards the cleaning procedure of the waxing. This product will be used to filter the dirt such as grime and hairs. Our product is MAGIC PARAFFIN WAX FILTER (MPWF).